Effects of internal pore pressure on closed-cell elastomeric foams - Lopez Pamies, Oscar (2012)
A micromechanics framework for porous elastomers with internal pore pressure (Idiart and Lopez-Pamies, 2012) is used together with an earlier homogenization estimate for elastomers containing vacuous pores (Lopez-Pamies and Ponte Casta~neda, 2007) to investigate the mechanical response and stability of closed-cell foams. Motivated by applications of technological interest, the focus is on isotropic foams made up of a random isotropic distribution of pores embedded in an isotropic matrix material, wherein the initial internal pore pressure is identical to the external pressure exerted by the environment (e.g., atmospheric pressure). It is found that the presence of internal pore pressure significantly stiffens and stabilizes the response of elastomeric foams, and hence that it must be taken into account when modeling this type of materials.